Mating-induced differential coding of plant odour and sex pheromone in a male moth - Barrozo, Romina (2011)
Innate behaviours in animals can be influenced by several factors, such as the environment, experience, or physiological status. This behavioural plasticity originates from changes in the underlying neuronal substrate. A well-described form of plasticity is induced by mating. In both vertebrates and invertebrates, males experience a post-ejaculatory refractory period, during which they avoid new females. In the male moth Agrotis ipsilon, mating induces a transient inhibition of responses to the female-produced sex pheromone. To understand the neural bases of this inhibition and its possible odour specificity, we carried out a detailed analysis of the response characteristics of the different neuron types from the periphery to the central level. We examined the response patterns of pheromone-sensitive and plant volatile-sensitive neurons in virgin and mated male moths. By using intracellular recordings, we showed that mating changes the response characteristics of pheromone-sensitive antennal lobe (AL) neurons, and thus decreases their sensitivity to sex pheromone. Individual olfactory receptor neuron (ORN) recordings and calcium imaging experiments indicated that pheromone sensory input remains constant. On the other hand, calcium responses to non-pheromonal odours (plant volatiles) increased after mating, as reflected by increased firing frequencies of plant-sensitive AL neurons, although ORN responses to heptanal remained unchanged. We suggest that differential processing of pheromone and plant odours allows mated males to transiently block their central pheromone detection system, and increase non-pheromonal odour detection in order to efficiently locate food sources.